SHOCK TEMPERATURE IN CALCITE (CACO3) AT 95-160 GPA - Gupta S.C.; Love S.G.; Ahrens T.J. (My University, 2002)
The temperatures induced in crystalline calcite (CaCO3) upon planar shock compression (95–160 GPa) are reported from two-stage light gas gun experiments. Temperatures of 3300–5400 K are obtained by fitting six-channel optical pyrometer radiances in the 450–900 nm range to the Planck gray-body radiation law. Thermodynamic calculations demonstrate that these temperatures are some 400–1350 K lower than expected for vibronic excitations of the lattice with a 3R/mole-atom specific heat (R is gas constant). The temperature deficit along the Hugoniot is larger than that expected from only melting. In addition to melting, it appears likely that shock-induced decomposition of calcite occurs behind the shock front. We modeled disproportionation of calcite into CaO (solid) plus CO2 (gas). For temperature calculations, specific heat at constant volume for 1 mole of CO2 is taken to be 6.7R as compared to 9R in the solid state; whereas a mole of calcite and a mole of CaO have their solid state values 15R and 6R, respectively. Calculations suggest that the calcite decomposes to CaO and CO2 at ∼110±10 GPa along the Hugoniot. Recent reanalysis of earlier VISAR measurements of particle velocity profiles [1] indicates that calcite shocked to 18 GPa undergoes disproportionation at much lower pressures upon isentropic expansion.